Docentes propiciadores de ambientes educativos para una Cultura de Paz en la Primera Infancia - Guevara Salazar, Leidy Ximena (Universidad Santiago de Cali, 2017)
The stay in the educational institutions for students is an important time, there they spend the years of childhood and youth, it is worth not only being the place to acquire and contribute to knowledge, school is the space for socializa-tion , That is identified as a space for debate, the solution of conflicts by way of respect, that is, that although as every scenario is permeated by tensiona that occur due to the differences of ages, students, teachers, administrative - in or-der to achieve the objectives of school work, the relationships that exist there, it is in the school where one learns to communicate, to listen, to respect differ-ences, to propose, to make good use of physical spaces, to Take care of nature, that is to live together. Taking into account that the first years of life from 0 to 6 years are ideal for learning, to model the behavior that will guide the be-havior in adult life for this reason, that the processes, pedagogical practices and curricular criteria of an Educational Institution Guarantee environments conducive to peace in childhood.